TOKOH ULAMA HADIS DI MALAYSIA - Muhammad Fajri Yusuf (Al-Thiqah: Journal of Hadith and Prophetic Tradition, 2024)
Kassim Ahmad is a multi-talented intellectual. He is known as a poet, cultural expert and reliable politician. Kassim''s interest in politics and philosophy introduced him to the La Rouche political-philosophical movement in the United States. The anti-hadith movement in Malaysia emerged in the 1980s which was spearheaded by Kassim Ahmad. The thoughts of Inkar Sunnah Kassim Ahmad can be seen in his book "Hadith One Reassessment" (HSPS). This controversial book comes from his lectures at the Department of Anthropology and Sociology of the National University of Malaysia (UKM). The question is who is Kassim Ahmad, what is Kassim Ahmad''s sunnah inkar thinking and why Kassim Ahmad''s thinking has received a wide response in society These questions are what we want to answer in this study. This study uses the library research method.The Inkar Sunnah school led by Kassim Ahmad is a heretic. This is because this school has rejected the sahih hadith as a source of Islamic law, insulted the Prophet Muhammad as the Prophet, and distorted the meaning of the verses of the Qur''an according to their wishes. The arguments put forward by Kassim Ahmad in rejecting the hadith are wrong. This mistake was identified as the result of their superficiality in understanding Islam and its teachings holistically.The socialization of the teachings of the Sunnah in Malaysia is carried out in various ways, namely published the Treatise of lqra'', published articles in print and internet media, discussions, scientific forums, lectures and so on